THE LEGAL FOOTING OF PETOK D AS THE EVIDENCE OF LAND OWNERSHIP AND RIGHTS - Margareta, Stefani; Huda, Miftakhul (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2023)
Land tenure is not only physically owned, but juridical ownership is also required. One of the policies that the government can implement is to provide legal certainty and protection of ownership of land rights as regulated in Government Regulation No. 24/1997 concerning land registration. This research aims to determine the characteristics of evidence on land ownership that can be recognized as a certificate and to find out how judges' ratio decided a certificate as the evidence of ownership. The method used in this research is the juridical-normative research method which is the legal research to examine issues from the norm’s perspective. The approach of this research are statutory, conceptual, and case approaches. Based on the research findings, it can be concluded that the characteristics of ownership of land rights evidence that are recognized as exceeding certificates are the acquisition of land objects based on legal rights, details of land history based on evidence, physical possession of land, evidence of land object tax payments and the existence of witness statements of residents related to physical land tenure; The judge's ratio decidendi overriding the land certificate means that, the Defendant/Plaintiff in the counterclaim can prove the acquisition of land plot objects along with a clear history of the land.